Cumulative incidence and risk factors for limber tail in the Dogslife labrador retriever cohort. (17th September 2016) - Pugh, C. A.; de C. Bronsvoort, B. M.; Handel, I. G.; Querry, D.; Rose, E.; Summers, K.; Clements, D. N.
Abstract : Limber tail is a condition that typically affects larger working breeds causing tail limpness and pain, resolving without veterinary intervention. It is poorly understood and the disease burden has not been well characterised. Data collected from owners of the Dogslife cohort of Labrador Retrievers have been used to describe incidents and a case–control study was undertaken to elucidate risk factors with 38 cases and 86 controls. The cumulative incidence of unexplained tail limpness was 9.7 per cent. Swimming is not a necessary precursor for limber tail, but it is a risk factor (OR=4.7) and working dogs were more susceptible than non‐working dogs (OR=5.1). Higher latitudes were shown to be a risk factor for developing the condition and the case dogs were more related to each other than might be expected by chance. This suggests that dogs may have an underlying genetic predisposition to developing the condition. This study is the first, large‐scale investigation of limber tail and the findings reveal an unexpectedly high illness burden. Anecdotally, accepted risk factors have been confirmed and the extent of their impact has been quantified. Identifying latitude and a potential underlying genetic predisposition suggests avenues for future work on this painful and distressing condition.